Anteseden dan Konsekuensi dari Variabel Kolaborasi Internal dan Eksternal Terhadap Transformasi Digital UMKM - Wisnu Yuwono; Shelly Rosalina; Lady Lady (Journal of Business and Economics Research (JBE), 2026)
This research investigates the influence of knowledge-skill, financial availability, digital maturity, social media on digital transformation by incorporating internal-external collaboration (IEC) as mediating construct. This study adopts quantitative approach, with data obtained from 353 MSME respondents in various regions of Indonesia using convenience and purposive sampling. Data analysis was conducted using PLS-SEM method. The findings indicate that financial availability (t = 7,180, p < 0,05), digital maturity (t = 2,322, p < 0,05), and social media (t = 2,204, p < 0,05) have a positive effect on IEC, while knowledge-skill does not have a positive effect. Furthermore, knowledge-skill (t = 2,669, p < 0,05), digital maturity (t = 4,198, p < 0,05), and IEC (t = 2,165, p < 0,05) are found to positively affect digital transformation, while financial availability and social media do not have a positive effect. In terms of indirect relationships, only financial availability demonstrates a positive impact on digital transformation through IEC (t = 2,047, p < 0,05). These results suggest that IEC plays a crucial role in mitigating financial resource constraints in the digital transformation process. The novelty lies in the incorporation of IEC as a mediating variable in the context of MSMEs’ digital transformation, a topic that remains relatively underexplored in prior research. This study contributed to the enrichment of the MSME digital transformation literature by emphasizing the mediating role of IEC. Moreover, the findings offer practical implications for MSME practitioners and stakeholders in formulating more focused and sustainable digitalization strategies.